PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA TOKO BANGUNAN UD. WIJAYA KUSUMA - I Gede Agus Sentana Widana Yasa; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Employee performance in the company is a very important thing to be used as a benchmark forachievement in the company. The performance of employees in each company has different criteria according to the provisions of the company. The potential possessed by individuals also affects the level ofperformance produced by employees, where this potential can motivate employees to work optimally towards the company's operational activities, and can influence better employee work results. This study aims to analyze and explain the influence of work motivation, work discipline, and compensation on employee performance at the UD Building Store. Wijaya Kusuma. The sample in this research is 30 employees. Data analysis using multiple linear regression analysis techniques to answer the problem formulation with the help of the SPSS program. The results of testing the hypothesis show that the variables: 1) Work motivation has a positive and significant effect on employee performance at the UD Building Store. Wijaya Kusuma, 2) Work discipline has a positive and significant effect on the performance of employees at the UD Building Store. Wijaya Kusuma, 3) Compensation has a positive and significant effect on employee performance at the UDBuilding Store. Wijaya Kusuma.